Kontra of pro evolusie en evolusionisme? Drie Christelike bioloë se besinning oor die ontstaan en ontwikkeling van die wêreld en die mens - van der Walt, B. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2016)
Contra or pro evolution and evolutionism? Three Christian biologists’ reflections on the origen and development of the world and the human being The viewpoints of the following three prominent natural scientists within the Reformed Christian tradition on the origin and evolution of the world are discussed in this essay: the Dutch zoologist, J. Harry Diemer (1904-1945), J.J. Duyvené de Wit (1909-1965), professor at the erstwhile University of the Orange Free State, and Jan Lever (1922-2010) from the Free University in Amsterdam1. Their viewpoints reveal some similarities as well as radical differences. They all started with A. Kuyper’s (1837-1920) viewpoint on evolution and evolutionism in 1899 but developed in different directions. Diemer’s contribution was his reaction against deistic and supernaturalist viewpoints about wonders. According to him wonders imply the hidden developmental potential or evolution of God’s miracles of creation, redemption and providence. According to De Wit, the correct question to be asked by Christians is not “creation or evolution?” The Bible acknowledges the genesis or unfolding of creation. Evolution is the temporal, continuing development of the already (before time) completed divine act of creation. However, De Wit very clearly argued contra evolutionism. Lever’s viewpoint is discussed in greater detail. He attempted to reconcile his evolutionary biology with the biblical idea of God as Creator. However, a growing tension between the two is evident and became more pronounced after about 1970, as is indicated in a next published article (cf. Van der Walt, 2016b).